Problems for equations with special parabolic operator of fractional differentiation - Matychuk, M. I. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
We establish the well-posedness of the Cauchy problem and the two-point boundary-value problem for an equation with an operator of fractional differentiation that corresponds to the singular parabolic Beltrami – Laplace operator on a surface of the Dini class.